Acara Bedah Rumah: Reduksi Orientasi Hidup “Menjadi” Ke Hidup “Memiliki” - Ida Bagus Made Satya Wira Dananjaya (Universitas Mahendradatta Denpasar, 2020)
Poor or pre-prosperous (henceforth will be called poor for the opposite of the wordrich or prosperous) is clearly not an ideal especially the purpose of life, seeing the shock ofadvertisements and electronic cinema that displays thick boundaries between rich-poor certainlyrich more tempting and tantalizing. Fantasy of life Rich men fall in love with poor women apartfrom predictable story lines implying a desire for rich is more highlighted on television.Likewise, the rich who are kind or evil, also against the character of the poor, almost becomedecoration on television. Rich character means to have while poor does not have. In short, inIndonesian television, these two socio-economic identities are always clashed, swiped at thesame time triggering micro commotion. Having various coefficient facilities by laying offconvenience, fame, elite, that is the picture of being rich on television, but it does not mean thatthe opponents of the rich are liable or not figures. main. The film Cemara Family, at least candisturb the established storyline of the confrontation of the rich and the poor. The poor figureplayed by Abah and his family gets the most camera shots about the trinkets of his life.Simplicity is even more to the disadvantages, selling snacks while schooling, a pedicab driver isa picture of Abah's life and family. The question then is to sell poverty on television? or aquestion that requires a more technical answer to how poor can be sold on television?